Amplitude of Low-Frequency Fluctuation in Multiple Frequency Bands in Tension-Type Headache Patients: A Resting-State Functional Magnetic Resonance Imaging Study - Li, Meng-Ting; Zhang, Shu-Xian; Li, Xue; Antwi, Collins Opoku; Sun, Jia-Wei; Wang, Chao; Sun, Xi-He; Jia, Xi-Ze; Ren, Jun (Frontiers in Neuroscience, 2021)
Abstract Purpose: Tension-type headache (TTH), the most prevalent primary headache disorder, imposes an enormous burden on the people of the world. The quest to ease suffering from this neurologic disorder has sustained research interest. The present study aimed at evaluating the amplitude of low-frequency oscillations of the brain in multiple frequency bands in patients with tension-type headache. Methods: To address this question, 63 participants were enrolled in the study, including 32 TTH patients and 31 healthy controls. For all the participants, amplitude of low-fluctuation (ALFF) was measured in six frequency bands (conventional frequency bands: 0.01-0.08 Hz, slow-2: 0.198-0.25 Hz, slow-3: 0.073-0.198 Hz, slow-4: 0.027-0.073 Hz, slow-5: 0.01-0.027 Hz, slow-6: 0-0.01 Hz), and the differences between TTH patients and healthy controls (HCs) were examined. To explore the relationship between the altered ALFF brain regions in the six frequency bands and the Visual Analogue Scale (VAS) score in the TTH patients, a Pearson correlation analysis was performed. Results: In all the six frequency bands, decreased ALFF value was detected and regions showing reduced ALFF value were mostly located in middle frontal gyrus and superior gyrus. Frequency dependent alternating characterization of intrinsic brain activity was found in the left caudate nucleus in the slow-2 band of 0.198-0.25 Hz and in the right inferior frontal orbital gyrus in the slow-5 band of 0.01-0.027 Hz. For the correlation results, both left anterior cingulate and paracingulate gyri and right superior parietal gyrus showed positive correlation with the VAS score in the slow-4 frequency band of 0.027-0.073 Hz. Conclusion: The ALFF alterations in the brain regions of TTH patients are involved in pain processing. The altered low-frequency oscillations in the multiple regions may help promote the understanding of the pathophysiology of TTH. These observations could also allow the future treatment of TTH more directional and targeted, and promote the development of TTH treatment.